Copper(II) Complexes of 2-Cyclohexylaminopyridine N-Oxide - X. West, Douglas (Asian Journal of Chemistry, 2010)
Five copper(II) salts have been used to prepare complexes of 2- cyclohexylpyridine N-oxide. Their stoichiometries have been established by partial elemental analyses, and their ir, uv-vis-nir and esr spectra, along with other physical properties, are reported. The nature of these new compounds is compared to previously reported 2-alkylpyridine N-oxide copper(II) complexes.